2013
DOI: 10.1111/dmcn.12125
|View full text |Cite
|
Sign up to set email alerts
|

The crucial role of the predictability of motor response in visuomotor deficits in very preterm children at school age

Abstract: DCDDevelopmental No group difference in visuomotor performance was present for the structured condition. In the non-structured condition, children born very preterm with and without a research diagnosis of DCD had poorer visuomotor performance than those born at term. INTERPRETATIONThe predictability of the required motor response plays a crucial role in visuomotor deficits in very preterm children, regardless of DCD status.Children born very preterm (<32wks' gestation) are vulnerable to poor visuomotor develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
0
17
0
2
Order By: Relevance
“…An infant’s inability to align the head with the body during the pull-to-sit maneuver or stabilize the head in prone could suggest low or high muscle tone, an imbalance between neck flexors and extensors, poor postural stability, or abnormal sensory processing such as abnormal feedback from the vestibular-ocular righting system [11,12]. Recent studies have also noted the significant impact of poor coupling between early motor patterns and vision in preterm infants and later delays in school related motor responses and visuomotor tasks [27,28]. Furthermore, Karch et al [29] found that stereotypy scores of upper limb movements in 3-month-old infants identified cerebral palsy cases with 90% sensitivity and 96% specificity at 2 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…An infant’s inability to align the head with the body during the pull-to-sit maneuver or stabilize the head in prone could suggest low or high muscle tone, an imbalance between neck flexors and extensors, poor postural stability, or abnormal sensory processing such as abnormal feedback from the vestibular-ocular righting system [11,12]. Recent studies have also noted the significant impact of poor coupling between early motor patterns and vision in preterm infants and later delays in school related motor responses and visuomotor tasks [27,28]. Furthermore, Karch et al [29] found that stereotypy scores of upper limb movements in 3-month-old infants identified cerebral palsy cases with 90% sensitivity and 96% specificity at 2 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…As a larger proportion of children born EPT had mothers born in non-Nordic countries (p < 0.01) and who had lower educational levels (p < 0.01), the analyses were run again adjusting for these factors. The results remained similar, with a mean (standard error) of 88 (AE1) and 99 (AE1) VMI score (p < 0.001), a mean difference of 11 points (95% CI [8][9][10][11][12][13][14] and an effect size of g 2 = 0.06. Mild VMI impairment was detected in 142 of 355 (40%) children born EPT and in 45 of 364 (12%) control children born at term, with an odds ratio of 0.21 (95% CI 0.15-0.31, p < 0.001).…”
Section: Comparison Of Vmi Scores Between the Two Groupsmentioning
confidence: 83%
“…All of these domains are known to pose difficulties for children born EPT. Several studies have reported lower VMI in preterm‐born children , but few studies have evaluated VMI at school‐age in large cohorts of exclusively EPT children born in the 2000s.…”
Section: Introductionmentioning
confidence: 99%
“…Outcome measures 2.6.1. Primary outcomes Well-validated, mostly computerised, (adaptations of) widely used tests were selected to provide a comprehensive assessment of neurocognitive functioning, according to recent recommendations [15]: attention [16], processing speed [16], memory [17e19], executive functioning (EF) [20], visuomotor integration (VMI) [21], and intellectual functioning (Table 1) [17,18]. For a detailed description of the tests, see Appendix.…”
Section: Methodsmentioning
confidence: 99%